PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF TWO COMMON TERRESTERIAL MEDICINAL PLANTS RUTA CHALEPENSIS AND RUMEX NERVOSUS - Kasimala, Madhu Babu; Tukue, Merih; Ermias, Robiel (BALI MEDICAL JOURNAL; Vol 3 No 3 (2014), 2014)
Background: Ruta chalapensis and Rumex nervosus are used as an extensive household remedy for  various diseases in Eritrea. The components of these plants are of great interest in medicinal  chemistry. Leaves and young stems of Ruta and Rumex have been reported to contain alkaloids,  flavonoids, phenols, amino acids, furanocoumarins and saponins. Various solvents like ethanol,  acetone and aqueous extracts of the two plants were screened for the presence of bioactive  compounds. Methods: The antibacterial activities of these extracts were investigated against  Staphylococcus aureus , a gram positive bacteria and Escherichia coli, gram negative bacteria. The  antibacterial activity was tested using Muller Hinton Agar medium by disc diffusion method and  minimum inhibitory concentration assays. Results: After incubation, zone of inhibition was measured  in mm, a good inhibition (>5mm) was observed indicating the effective antibacterial activity of the  bioactive compounds in both the plant extracts.
Keywords: Ruta chalapensis, Rumex nervosus, E. coli, S. aureus, anti microbial activity, phytochemical screening.